Strategi Peningkatan Occupancy Rate dan Average Room Rate pada Masa Pandemi Covid-19 di Hotel Noormans Semarang - Izza Ulumuddin Ahmad Asshofi; Prima Setia Judha Pranata (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2020)
The Covid-19 pandemic has caused unrest for all citizens of the world in the health, trade, economy, security, politics, transportation, human mobility and tourism sectors. As the second largest contributor to foreign exchange in Indonesia in 2019, tourism, especially hospitality, has experienced a significant decline in business. Starting from canceling room reservations to canceling various activities at the hotel. As a consequence, the hotel occupancy rate and average room rate dropped dramatically to 10% - 25%. This was also experienced by Hotel Noormans Semarang, which only had an occupancy rate of 15% in April 2020 with an average room rate below the price of IDR 300,000.00. The aim of this paper is to observe the strategy to increase the occupancy rate and average room rate during the Covid-19 pandemic at the Hotel Noormans Semarang. This research was designed with a descriptive qualitative paradigm. This research shows that the strategy of increasing the occupancy rate and average room rate during the pandemic at Noormans hotels in 2020 does not show positive results. However, what happened was the opposite, a decline from 2019 to 2020. The occupancy rate decreased from 70% to 36% and the average room rate decreased from IDR 332,094.00 to IDR 258,250.00. Keywords: occupancy rate, average room rate, hotel, Covid-19